Risperidone plasma concentrations are associated with hyperprolactinemia in autism spectrum disorder children: The impact of CYP2D6 polymorphisms. (August 2022) - Chamnanphon, Monpat; Vanwong, Natchaya; Prommas, Santirhat; Koomdee, Napatrupron; Sukprasong, Rattanaporn; Rachanakul, Jiratha; Nuntharadthanaphong, Nutthan; Hongkaew, Yaowaluck; John, Shobana; Ngamsamut, Nattawat; Nuntamool, Nopphadol; Limsila, Penkhae; et al.
Abstract: Background: Risperidone causes hyperprolactinemia by blocking D2 receptors on lactotrophs anterior pituitary, which prevents prolactin secretion inhibition. Risperidone is converted to 9-hydroxyrisperidone by the CYP2D6 enzyme. Polymorphisms in CYP2D6 may affect serum prolactin and could be a predictor of hyperprolactinemia. The goal of this study was to see if there was an association between CYP2D6 variants, risperidone dose, clinical data and serum prolactin levels in Thai children and adolescents with autism spectrum disorder (ASD). Method: In 107 Thai ASD patients on risperidone, allele-specific primer extension and multiplex PCR platforms were used to genotype the CYP2D6 gene. The chemiluminescence immunoassay (CLIA) technique was used to measure fasting serum prolactin levels. Results: The median serum prolactin level was 16. 25 ng/mL (IQR; 10. 43-22. 18), and patients with CYP2D6*1/*5 (6. 54%) had substantially lower prolactin levels than those with CYP2D6*1/*1 [median; 11. 2 ng/mL (IQR; 3. 95-21. 10) vs. 21.3 (IQR; 14. 43-32. 18), p =0. 032]. CYP2D6*1/*10, *10/*10, and *10/*41 produced less prolactin than *1/*1 ( wild type). Furthermore, gender and risperidone dose were associated with significantly different prolactin levels with p -value 0. 02 and 0. 006, respectively. Multivariate analysis showed a significant association of serum prolactin level with body mass index and risperidone dose ( p <0.05). Conclusions: Our study showed that CYP2D6 carriers of absent and decreased functional alleles had lower serum prolactin levels in Thai ASD patients treated with risperidone treatment; this is important to clinicians, indicating that they should consider about CYP2D6 genotyping before beginning risperidone in ASD patients. CYP2D6 genotypes might be a predictor for levels of prolactin in clinical treatment. Highlights: The CYP2D6 polymorphisms influence serum prolactin concentrations in Thai ASD patients treated with risperidone. Result suggests that high doses of risperidone result in elevated serum prolactin levels. Clinicians expected fewer side effects in Thai ASD male patients treated with risperidone harboring reduced CYP2D6 activity.